Strategi Pengembangan Wakaf Berkelanjutan dalam Sektor Pertanian: Studi Kasus di Yayasan Pemeliharaan dan Perluasan Wakaf Pondok Modern (YPPWPM) Gontor Ponorogo - Cahyo, Eko Nur; Muqorobin, Ahmad (Falah: Jurnal Ekonomi Syariah, 2019)
The development of endowments land in the agricultural sector is very essential because it is one of the strengthening sectors of the Indonesian economy. This study aims to identify the development of sustainable endowment strategies through the agricultural sector at Yayasan Pemeliharaan dan Perluasan Wakaf Pondok Modern (YPPWPM), Pondok Modern Darussalam Gontor Ponorogo. To identify the endowments development strategies in the agricultural sector this research is qualitative. The result shows that Yayasan Pemeliharaan dan Perluasan Wakaf Pondok Modern (YPPWPM), Pondok Modern Darussalam Gontor Ponorogo carried out three-factor systems for the sustainable development strategy. First, using the waqf land rental system. Second, the development of the management system. and thirdly, the profit-sharing system with the concept of mazara'ah. On the other hand, the results of the SWOT analysis indicate that this model is worth continuing to develop sustainable endowments so that the benefits of endowments can be fulfilled continuously.